Chronic Lymphocytic Leukaemia/Small Lymphocytic Lymphoma with Hyperleukocytosis: A Case Report - Mandal, Ankit Kumar; Sah, Priya; Dhakal, Sanam; Sapkota, Sulav; Parajuli, Surya Bahadur (Annapurna Journal of Health Sciences, 2023)
Chronic lymphocytic leukaemia/small lymphocytic lymphoma (CLL/SLL) is a B-cell lymphocytic neoplasm with indolent clinical course. Author describes a 55-yearold male presenting with fever and generalized lymphadenopathy, found to have white cell count of 576000/mm3 and subsequently was diagnosed with CLL/SLL. The patient received systemic chemotherapy in our department, got clinically improved and on follow-up clinic visit documented normalisation of his white cell counts. The case report brings up a rare presentation of CLL/SLL with such high white cell count and being reported from Nepal. We don't have such cases reported in our literature.